Bioinformatic analysis identifies HPV-related tumor microenvironment remodeling prognostic biomarkers in head and neck squamous cell carcinoma - Zhou, Qimin; Yuan, Ouyang; Cui, Hongtu; Hu, Tao; Xiao, Gary Guishan; Wei, Jiao; Zhang, Honglei; Wu, Chengjun (Frontiers in Cellular and Infection Microbiology, 2022)
Head and neck squamous cell carcinomas (HNSCCs) are highly aggressive tumors with rapid progression and poor prognosis. Human Papillomavirus (HPV) infection has been identified as one of the most important carcinogens for HNSCC. As an early event in HNSCC, infection with HPV leads to altered immune profiles in the tumor microenvironment (TME). TME plays a key role in HNSCC progression and transformation. However, the TME in HNSCC is a complex and heterogeneous mix of tumor cells, fibroblasts, different types of infiltrating immune cells, and extracellular matrix. Biomarkers relevant to TME, and the biological role of these biomarkers, remain poorly understood. To this end, we performed comprehensive analysis of RNA-Seq data from tumor tissue of 502 HNSCC patients and healthy tissue of 44 control samples. In total, we identified 4237 differently expressed genes, including 2062 up-regulated and 2175 down-regulated genes. Further in-depth bioinformatic analysis suggested 19 HNSCC tumor tissue specific genes. In the next analysis, we focused on the biomarker candidates shown to be significantly associated with unfavorable patient survival - ITGA5, PLAU, PLAUR, SERPINE1, TGFB1, and VEGFC. We found that expression of these genes was negatively regulated by DNA methylation. Strikingly, all of these potential biomarkers are profoundly involved in the activation of the EMT pathway in HNSCCs. In addition, these targets were found to be positively correlated with immune invasion levels of CD4+ T cells, macrophages, neutrophils and dendritic cells, while negatively correlated with B cells infiltration and CD8+ T cells invasion. Notably, our data showed that the expression level of ITGA5, PLAU, PLAUR, SERPINE1 and TGFB1 were significantly overexpressed in HPV positive HNSCCs compared to normal controls, indicating the potential roles of these biomarkers as transformation and/or malignant progression markers for HNSCCs in patients with HPV infection. Taken together, the results of our study propose ITGA5, PLAU, PLAUR, SERPINE1 and TGFB1 as potential prognostic biomarkers for HNSCCs, which might be involved in the HPV related TME remodeling of HNSCC. Our findings provide important implications for the development and/or improvement of patient stratification and customized immunotherapies in HNSCC.